Shift of combined ecotoxicity index in petroleum polluted soils during a bacterial remediation - Chai, Xiaoyun; Wang, Mutian; Fu, Xiaowen; Zhang, Wen; Huang, Yujie; Germaine, Kieran J.; Wang, Jianing (Frontiers in Environmental Science, 2023)
Bioremediation has been shown to be an effective strategy for removing toxic pollutants from the environment, particularly organic chemicals such as petroleum hydrocarbons. This paper investigates the changes in toxicity of petroleum-contaminated soil as a result of microbial remediation processes. Changes in the ecotoxicity of the contaminated soil were examined using a plant, earthworm, enzyme activity and luminescent bacteria toxicity tests. The results showed that bioremediation could effectively degrade petroleum hydrocarbon (C10-C40) pollutants. After 42 days of remediation, the petroleum hydrocarbon (C10-C40) content of Group A (bioaugmented polluted wetland soil) decreased from 1.66 g/kg to 1.00 g/kg, and the degradation rate was 40.64%. The petroleum hydrocarbon (C10-C40) content of Group B (bioaugmented polluted farmland soil decreased from 4.00 g/kg to 1.94 g/kg, and the degradation rate was 51.56%. During the microbial remediation progress, the ecological toxicity of petroleum-contaminated soil first increased and then decreased. The photosynthetic pigment content index in the toxicity test of higher plants, the survival rate index earthworms, and the soil catalase activity, all showed good consistency with the relative luminescence index of DCM/DMSO extracted in the toxicity test of luminescent bacteria. The soil toxicity decreased significantly after remediation. Specifically, the photosynthetic pigment content of wheat were inhibited in the soil during the whole process (remediation for 42 days), and decreased to the minimum on remediation day 21. The 7-day and 14-day survival rate of earthworms in Group A and Group B gradually decreased in the soil remediation process, then gradually increased, survival rate at the end of remediation was higher than at the beginning. Soil catalase activity was significantly negatively correlated with petroleum hydrocarbon (C10-C40) content (-0.988, -0.989). The ecological toxicity of contaminated soil reached to the maximum on the 21 st day of remediation, relative luminosity of luminescent bacteria in dichloromethane/dimethyl sulfoxide extracts from Group A and Group B were 26.3% and 16.3%, respectively. Wheat photosynthetic pigment content, earthworm survival rate, soil catalase activity and relative luminescence of luminescent bacteria can better indicate the ecological toxicity of petroleum-contaminated soil in bioremediation process.